SOME FELLER SEMIGROUPS ON C_∞ (R^n× Z^m) GENERATED BY PSEUDO-DIFFERENTIAL OPERATORS. Issue 2 (15th April 2015) - Evans, Kristian P.; Jacob, Niels; Shen, Chenglin
Abstract : In this paper we construct some Feller semigroups, hence Feller processes, with state space R^n× Z^m starting with pseudo-differential operators having symbols defined on R^n× R^n× Z^m× T^m .